Logro de la comprensión y producción de textos expositivos en estudiantes del quinto grado en dos instituciones educativas públicas de secundaria, distrito Ramón Castilla 2021 - Cabrera Ysuiza, Diana Iris (2023)
The objective of this research was to describe the level of achievement of the comprehension and production of expositives texts in fifth grade students in two public secondary institutions, Ramón Castilla, 2021. The study is framed in the quantitative and descriptive approach. The simple descriptive design Ox, y was used. The population consisted of 296 students. The sample was 169 students. To measure the level of achievement of expositive text comprehension, the questionnaire instrument was used. To measure the level of achievement of the production of expositive texts, the performance test was used, with its respective evaluation rubric. The results found indicate that the level of achievement of the comprehension and production of expositive texts is at the beginning (98.2%) in the students of the fifth grade of secondary school in two public secondary educational institutions of the district of Caballo Cocha, 2021. Concludes that the learning of the comprehension and production of expositive texts is not developed at acceptable levels in the students evaluated.